The Safety Profile of General and Local Anaesthetic Agents: Data Collected during 20 Years of Spontaneous Reporting Activities in the Campania Region (Southern Italy) - Francesca Gargano; Cristina Scavone; Gabriella di Mauro; Alberto Della Corte; Alice Zoccoli; Francesco Rossi; Giovanni Francesco Nicoletti; Annalisa Capuano (MDPI AG, 2021)
Background: General and local anaesthetics are widely used during surgery. These drugs have peculiar safety profiles, being commonly associated with mild and reversible local adverse drug reactions (ADRs), but also with more severe and systemic ADRs, including respiratory and cardiovascular depression and anaphylaxis. Methods and Objectives: We carried out a descriptive analysis of Individual Case Safety Reports (ICSRs) sent to the Campania Regional Centre of Pharmacovigilance (Southern Italy) from 2001 to 2021 that reported general or local anaesthetics as suspected drugs, with the aim of describing their overall characteristics, focussing on the ADRs' seriousness and distribution by System Organ Class (SOC) and Preferred Term (PT). Results: A total of 110 ICSRs documenting general or local anaesthetics were sent to the Italian pharmacovigilance database during 20 years of spontaneous reporting activities in the Campania region. ADRs mainly occurred in patients with a median age of 48 years and in a slightly higher percentage of men. ADRs were more commonly classified as not serious and had a favourable outcome. In terms of ADRs' distribution by SOC and PT, both general and local anaesthetics were associated with general and cutaneous disorders, with common ADRs that included lack of efficacy, rash, and erythema. In addition, general anaesthetics were associated with the occurrence of respiratory ADRs, while local anaesthetics were associated with the occurrence of nervous ADRs. Conclusion: Even though a limited number of ICSRs documenting anaesthetics-induced ADRs were retrieved from the Italian spontaneous reporting database in the Campania region, we believe that the continuous monitoring of these drugs is highly recommended, especially among the frail population.